Renacuajo de la rana de cristal Hyalinobatrachium colymbiphyllum (Anura: Centrolenidae) - Jaramillo, Fidel E (Universidad de Costa Rica, 1997)
The tadpole of Hyalinobatrachium colymbiphyllum is distinguished from other Central American centrolenid tadpoles by its a1most lateral eyes, spiracle positíoned posteriorly towards the lateroventral regíon, margin of the upper beak nearly uniform, margin of the lower beak with very slight1y and uniformly distributed serrations, and anterodorsal area of the tail with a row or narrow strip of melanophores at each fin side.